What are features? An ontology-based review of the literature. (November 2016) - Sanfilippo, Emilio M.; Borgo, Stefano
Abstract: Feature-based product modeling is the leading approach for the integrated representation of engineering product data. On the one side, this approach has stimulated the development of formal models and vocabularies, data standards and computational ontologies. On the other side, the current ways to model features are considered problematic since it lacks a principled and uniform methodology for feature representation. This paper reviews the state of art of feature-based modeling approaches by concentrating on how features are conceptualized. It points out the drawbacks of current approaches and proposes a high-level ontology-based perspective to harmonize the definition of feature. Highlights: State of the art review about the conceptualization of features across engineering for product lifecycle modeling. Feature types and definitions are analyzed via ontology engineering methodologies. High-level approach for integrated knowledge representation in engineering.